Nanomaterialsin Medical Applications - Rabindranath Jana, Aditi Sinha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The nanomaterials are the materials within the nano dimension (1–100 nm scale) have remarkably new characteristics which may influence the changes of device structures, and systems with novel properties and functions.They may have potential applications in many sectors, e.g, healthcare, electronics, transportation, energy harvesting, space exploration etc. In healthcare sector, it has the possibilities to develop drug delivery, gene therapy, diagnostics, and many areas of research and development. In recent years nanomaterialshave been applied to human health with promising results, especially in the field of cancer treatment. It focuses on developing new methods of preventing, diagnosing and treating various diseases. These materials show very high efficiency in destroying cancer cells and drug delivery trials. So the nanomaterialsin the form of nanorobotmay be used as an alternative to traditional cancer therapy, mostly due to the fact that they allow cancer cells to be targeted specifically. Other potential applications of nanotechnology in medicine may include cell repair, blood clotting, immune properties development and subsequently to deliver vaccine antigens. A nano-knife may be used as an almost non-invasive method of destroying cancer cells with high voltage electricity. Carbon nanotubes are already a popular way of repairing damaged tissues and might be used to regenerate nerves in the future. There are endless applications of these materials. The main objectives of this article are to outline the potential uses of nanomaterialsin medicine and suggest their future prospects.